Fructo-Oligosaccharide Alleviates Soybean-Induced Anaphylaxis in Piglets by Modulating Gut Microbes - Chang, Meinan; Zhao, Yuan; Qin, Guixin; Zhang, Xiaodong (Frontiers in Microbiology, 2018)
Soybean-induced allergy has a severe threat to the health of humans and animals. Some commensal bacteria such as Lactobacillus and Bifidobacteria, were observed prevent and treat allergic diseases. Prebiotic oligosaccharides as a food/diet additive could enhance body health and performance though modulating gut microbiota and immune response. The purpose of the present study was to examine whether fructo-oligosaccharides (FOS) could alleviate soybean-induced anaphylaxis by modulating gut microbiota. 21d piglets were sensitized with a diet containing 5% soybean and 30% peeled soybean meal. 0.6%FOS was administered starting one day prior to sensitization and continuing everyday thereafter. Blood was collected to analyze immune indices; DNA samples isolated from fresh intestinal contents of middle jejunum (M-jejunum), posterior jejunum (P-jejunum), ileum and cecum, which were used for gene sequences based on 16s rRNA. Results showed that soybean antigen sensitized piglets presented an increase in glycinin-specific IgG and β-conglycinin specific IgG, as well as total serum IgG, IgE and occurrence of diarrhea. Interleukin-4 (IL-4) and IL-10 decreased, and interferon-γ (IFN-γ) increased in piglets fed FOS diet than those in piglets fed the soybean diet. Improvement of intestinal microbiota is mainly manifested in increasing the abundance of Lactobacillus and Bifidobacteria in M-jejunum and reducing the abundance of Proteobacteria in P-jejunum and ileum. The correlation analysis indicated that FOS decrease immune indices which were relative to key species of gut microbiota. These results suggest that consumption of FOS alleviate soybean antigen-induced anaphylaxis, which is associated with improvement of Lactobacillus and Bifidobacteria in M-jejunum and decline of Proteobacteria in P-jejunum and ileum of pigs.